Towards a Greener Radiology: A Comprehensive Life Cycle Assessment Framework for Diagnostic Imaging - Roletto Andrea; Savio Anna; Marchi Beatrice; Zanoni Simone (Environmental and Climate Technologies)
The increasing focus on environmental sustainability is becoming essential in the radiology sector, which is accredited for about 10 % of the healthcare industry’s carbon footprint. A multitude of research initiatives investigated the environmental impacts of diagnostic imaging. Life Cycle Assessment (LCA) stands as a prominent method for structural assessment of environmental impacts, offering a tool for examining the environmental consequences of specific processes. The aim of this study includes analysing existing LCA approaches in the literature to identify their limitations and to suggest a comprehensive LCA framework for diagnostic imaging. Of the original articles on environmental sustainability in radiology published since 2014, five have described an LCA approach. About the boundaries of their systems, all studies considered the electricity consumption of imaging equipment. Usage of consumables was included in 80 % (4/5) of the studies, as well as energy consumption of auxiliary equipment and Heating, Ventilation and Air Conditioning (HVAC) systems. Only 40 % (2/5) of articles considered waste generation, cleaning and disposal of products used during imaging activities. The articles also varied in their LCA approach, with different life cycle assessment methods. Insights from this analysis led to the identification of differences in LCA methodological approaches in imaging found in the literature. In addition, a new LCA framework designed to overcome the limitations observed in existing research was proposed, offering a more comprehensive analysis. The objective may be the development of more targeted strategies to reduce Greenhouse Gas (GHG) emissions associated with diagnostic procedures.